PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL SIMAS ERIC UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI GETARAN HARMONIS KELAS X SMA/MA - Rizki Ezra Manik; Mitri Irianti; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning device developed are learning device based on the Simas Eric model to enhance student cognitive study result on harmonic vibrations material class X SMA/MA, consisting of a RPP, LKPD, and Cognitive Study Result Test. The purpose of this research was to produce a learning device valid based on Simas Eric model on harmonic vibrations material. This type of research is a Research and Development (R&D) with a 4D model design. The research instrument used was the RPP validation assessment sheets, LKPD and Cognitive Study Result Test which were used by the validator to assess learning device. The data was collected by providing learning device to the validator to be validated using RPP validation sheets, LKPD and Cognitive Study Result Test. Data analysis in this research using descriptive analysis, by calculating the validity score of each indicator of the learning device. Based on the result of the validity data analysis, the average value of the validity of the lesson plan for the first meeting was 3,49 with a high category, lesson plan for the second meeting was 3,38 with a high category, and lesson plan for the third meeting was 3,39 with a high category. The average validity of LKPD 1 was 3,51 with a very high category, LKPD 2 was 3,54 with a very high category, and LKPD 3 was 3,47 with a high category. The average validity of Cognitive Study Result Test was 3,34 with a high category, so that the overall average learning device was 3,47 with a high category. Thus the learning device based on Simas Eric model is declared valid and suitable for use on harmonic vibrations material class X SMA/MA.Key Words: Physics Learning Device, Simas Eric Model, CognitiveSstudy Result,Harmonic Vibrations